An Analysis of transformation in South Africa post 1994 - Maritz, PJ; Venter, JCM (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2021)
The transition from South Africa under the policies of Apartheid to its future state has been led by the African National Congress and its allies. This transition has been driven by a process of radical transformation, often informed by revolutionary philosophies and policies, which in turn were translated into radicalism. Historically revolutionary transformation has often had national disorder as consequence. As this approach entails great risk, this study indicates the risks entrenched in revolutionary transformation, and proposes alternative approaches. A literary study of relevant pieces of policy, and the philosophy that led to their construction was done, with indication of how these pieces of policy incarnated themselves in the actions of relevant political actors. Here the clear and present danger of these policies came to the fore. Opposing philosophies were then researched, and realistic alternatives proposed. The study concluded in finding revolutionary transformation not only sub-optimal, but purposefully dangerous for the safety and stability of a country, and urgently proposed that the tried and tested alternatives be adopted and normalised. This study contributes to the ongoing issue of approaching change in South Africa. Few would deny that change was necessary in post-1994 South Africa, and this article does not challenge the need for change in any way. The article contributes to the broader field of national governance by analysing and critiquing the current approach to change, which is radicalism in the name of revolutionary transformation, and offering tried and tested alternatives, which would lead to change that is more stable, more consistent, and does not entail the same risk of death, destruction, and civil war that revolutionary transformation has brought about in states where it has previously been driven to its limits.